Perioperative Dexmedetomidine Fails to Improve Postoperative Analgesic Consumption and Postoperative Recovery in Patients Undergoing Lateral Thoracotomy for Thoracic Esophageal Cancer: A Randomized, Double-Blind, Placebo-Controlled Trial. (7th May 2020) - Mao, Yu; Sun, Xuemei; Si, Li; Chen, Lijian; Liu, Xuesheng; Zhang, Zhi; Gu, Erwei
Abstract : Objectives . Dexmedetomidine is widely used as an adjunct to general anesthesia. In this study, we evaluated the effects of perioperative dexmedetomidine infusion on postoperative analgesia in patients undergoing lateral thoracotomy for thoracic esophageal cancer. Methods . A total of 62 patients undergoing lateral thoracotomy for thoracic esophageal cancer were randomized to receive adjuvant therapy with either dexmedetomidine (0.5 μ g/kg intravenous bolus injection for 10 min before induction of anesthesia, followed by continuous infusion of 0.2–0.4 μ g/kg/h until the end of surgery, and 0.06 μ g/kg/h for 5 days after surgery) or equal volumes of saline. Acute postoperative pain was treated with patient-controlled intravenous sufentanil and flurbiprofen axetil. The primary outcomes of this study were the numbers of analgesic requirements in the first postoperative 72 h. Results . Perioperative dexmedetomidine did not decrease the numbers of analgesic requirements in the first postoperative 72 h (dexmedetomidine group: 12.14 ± 4.76, saline group: 10.89 ± 5.66; p = 0.367 ). Likewise, the groups did not differ with respect to total postoperative analgesic requirements, postoperative pain, perioperative inflammation, blood cell count, incidence of adverse events, surgical recovery (assessed at postoperative days 2 and 5 using the surgical recovery scale), length of hospital stay, hospital cost, incidence of chronic pain, or quality of life. Notably, dexmedetomidine had beneficial effects on decreasing intraoperative opioid consumption and improving postoperative sleep quality. Discussion . Perioperative dexmedetomidine has limited analgesic benefits in lateral thoracotomy for esophageal cancer when added to an opioid-based multimodal anesthetic regimen but can reduce opioid consumption.